2008
DOI: 10.1128/jvi.01191-08
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Organization of Rift Valley Fever Virus Revealed by Cryoelectron Tomography

Abstract: Rift Valley fever virus (RVFV) is a member of the Bunyaviridae virus family (genus Phlebovirus)and is considered to be one of the most important pathogens in Africa, causing viral zoonoses in livestock and humans. Here, we report the characterization of the three-dimensional structural organization of RVFV vaccine strain MP-12 by cryoelectron tomography. Vitrified-hydrated virions were found to be spherical, with an average diameter of 100 nm. The virus glycoproteins formed cylindrical hollow spikes that clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
126
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 49 publications
9
126
1
1
Order By: Relevance
“…Respiratory syncytial virus (RSV), vesicular stomatitis virus (VSV), and rabies virus have highly symmetric, helical RNPs, the structures of which determine the morphology of the rod-or bullet-shaped virus particles (22)(23)(24)(25). In contrast, spherical phlebovirus particles have T = 12 icosahedral symmetry that does not include the RNP (26). N-RNA multimers from (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory syncytial virus (RSV), vesicular stomatitis virus (VSV), and rabies virus have highly symmetric, helical RNPs, the structures of which determine the morphology of the rod-or bullet-shaped virus particles (22)(23)(24)(25). In contrast, spherical phlebovirus particles have T = 12 icosahedral symmetry that does not include the RNP (26). N-RNA multimers from (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The Gn-Gc heterodimer is the building block of 110 hexamers and 12 pentamers containing six and five of the Gn-Gc heterodimeric units, respectively. Together, these 122 capsomers make up the icosahedral shell of the virion, following a T ϭ 12 triangulation (13,24). Exposure of virions to the activating pH will lead to rearrangement of the metastable Gn-Gc heterodimer and concomitantly enforce the interactions between Gc subunits, resulting in the formation of a Gc homooligomer.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the RVFV virion, a 78-kDa protein consisting of pre-Gn and Gn regions has been identified as a third but minor structural component (27,60). Cryoelectron microscopy studies of RVFV virions showed that the viral envelope comprises 720 heterodimers of Gn (54 kDa) and Gc (56 kDa), forming 110 cylinder-shaped hexamers and 12 pentamers according to a Tϭ12 icosahedral lattice (13,24).…”
mentioning
confidence: 99%
“…However, the limited resolution (6.1 nm) impeded determination of the compositions of the capsomers. It remained unclear whether a single structural unit composed of both G N and G C forms both the five-and six-coordinated glycoprotein capsomers or whether G N alone forms some capsomers and G C alone forms the other capsomers (10). In addition, the organization of RNPs inside the virions could not be addressed.…”
mentioning
confidence: 99%
“…In fact, there exist conflicting reports about isolation of both heterodimers (32) and homodimers (36) from Triton X-100-solubilized UUKV virions. The structure of RVFV virions studied recently using electron cryo-tomography revealed five-and six-coordinated glycoprotein capsomers organized on a Tϭ12 lattice (10). However, the limited resolution (6.1 nm) impeded determination of the compositions of the capsomers.…”
mentioning
confidence: 99%